Living alone, living together : two essays on the use of housing - King, Peter, 1960- (Emerald Publishing, 2017)
This book considers how a dwelling can protect and promote both our anxieties and our relationships. Both essays use a non-traditional literature to explore being alone and being with others, rather than relying on the social science literature, and offer a distinct and original contribution to the housing studies literature.
Keywords: Housing.; elektronické knihy; electronic books